2022
DOI: 10.1002/pmrj.12760
|View full text |Cite
|
Sign up to set email alerts
|

Quality of clinical practice guidelines on interventional management of low back pain: A systematic review

Abstract: ObjectiveTo appraise the quality of low back pain (LBP) clinical practice guidelines (CPG) that include interventional management recommendations and to associate their quality with characteristics including publication year and creating organization.TypeSystematic Review.Literature SurveyLBP (subacute or chronic) CPGs in English (symptom based, governmental or professional society created, January 1990‐May 2020) were found using MEDLINE, EMBASE, CINAHL, Ortho Guidelines, CPG Infobase, ECRI, Guidelines Interna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…This systematic review was registered with PROS-PERO (registration number: CRD42020185582) and followed the guidelines set forth by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses statement (Figure 1). 10,11 Detailed methodology for the quality assessment of the CPGs has been previously published 10 and is summarized here. In brief, we searched for all pertinent CPGs in several databases.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…This systematic review was registered with PROS-PERO (registration number: CRD42020185582) and followed the guidelines set forth by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses statement (Figure 1). 10,11 Detailed methodology for the quality assessment of the CPGs has been previously published 10 and is summarized here. In brief, we searched for all pertinent CPGs in several databases.…”
Section: Methodsmentioning
confidence: 99%
“…The gathered recommendations were then organized within each treatment category based on AGREE II recommendation scores (described previously 10 ). CPGs that received "yes" only votes were included in the high-quality group, CPGs that received a mix of "yes" and "yes with modification" votes were included in the moderate-quality group, and any CPG that received a "no" vote was in the low-quality group.…”
Section: Organization Of Recommendationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The AGREE II instrument was published in 2009 as a revised version of the original AGREE instrument issued in 2001 20. Previous studies have shown that the quality of CPGs has varied 21–47. Some studies have indicated that the quality of CPGs depends on the publication year,25 type of development organisation21 and version of CPGs 26…”
Section: Introductionmentioning
confidence: 99%